2017
DOI: 10.1021/acs.biochem.7b00870
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Glycosylation Governs the Vertebrate COPII Protein Trafficking Pathway

Abstract: The COPII coat complex, which mediates secretory cargo trafficking from the endoplasmic reticulum, is a key control point for subcellular protein targeting. Because misdirected proteins cannot function, protein sorting by COPII is critical for establishing and maintaining normal cell and tissue homeostasis. Indeed, mutations in COPII genes cause a range of human pathologies, including cranio-lenticulo-sutural dysplasia (CLSD), which is characterized by collagen trafficking defects, craniofacial abnormalities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 101 publications
(339 reference statements)
3
67
0
Order By: Relevance
“…A number of clues suggest that O‐GlcNAcylation may more broadly control the protein machinery responsible for endocytic membrane traffic such as by control of coat proteins. Evidence for broad control of coat protein assembly and thus membrane traffic has been uncovered for coatomer protein complex (COP) II (COPII) and COPI‐mediated traffic between the ER and Golgi . Similarly, complex formation by proteins involved in tethering or fusion/fission of membranes such as SNAP‐29 and GRASP55 can be regulated by OGT, which can result in control of autophagosome interaction with endosome/lysosomes.…”
Section: Direct Control Of Endocytic Membrane Traffic By Metabolitesmentioning
confidence: 99%
“…A number of clues suggest that O‐GlcNAcylation may more broadly control the protein machinery responsible for endocytic membrane traffic such as by control of coat proteins. Evidence for broad control of coat protein assembly and thus membrane traffic has been uncovered for coatomer protein complex (COP) II (COPII) and COPI‐mediated traffic between the ER and Golgi . Similarly, complex formation by proteins involved in tethering or fusion/fission of membranes such as SNAP‐29 and GRASP55 can be regulated by OGT, which can result in control of autophagosome interaction with endosome/lysosomes.…”
Section: Direct Control Of Endocytic Membrane Traffic By Metabolitesmentioning
confidence: 99%
“…It is likely that these changes in cancer cell surface β1,6‐GlcNAc branching reflects perturbations in HBP flux or trafficking. Indeed OGT silencing interferes with intracellular protein transport as recently reported for coatomer COP (coat protein) I and COP II protein trafficking pathways . OGT silencing might impair vesicular trafficking, thus disrupting the glycosylation machinery and the correct localization of GTs and GHs.…”
Section: Discussionmentioning
confidence: 75%
“…The dramatic changes in GSLs composition consecutive to siOGT may originate from a modification of the trafficking or localization of biosynthetic enzymes rather than from modification of their expression levels. Vesicular trafficking is managed by many components among which the COP I and COP II complexes are pivotal, as discussed above . Recently, it has been shown that the multiprotein coatomer COP I and COP II are regulated by O ‐GlcNAcylation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, study of membrane traffic between the ER and ERGIC must occur using metazoan models, including Caenorhabditis elegans , Drosophila, zebrafish, rodents, and human cell lines. Moreover, particular emphasis must be placed upon the role of post‐translational modifications such as phosphorylation, ubiquitinylation, and glycosylation, all of which have been identified on COPII subunits, as well as regulators of COPII coat assembly and disassembly . Combining these efforts with structural approaches, both in vitro and in situ, will be critical to gaining a clear understanding of the mechanisms underlying the earliest step in secretory cargo trafficking.…”
Section: Discussionmentioning
confidence: 99%